Life cycle assessment of superheated steam drying technology as a novel cow manure management method. (1st September 2017) - Hanifzadeh, Mohammadmatin; Nabati, Zahra; Longka, Pairote; Malakul, Pomthong; Apul, Defne; Kim, Dong-Shik
Abstract: Common methods of managing dairy manure are directly applying it to the farm field as a fertilizer. For direct application without any type of treatment, the majority of nutrients in the manure run off to the local river and lake during precipitation periods. The algae bloom is one of the environmental outcomes due to eutrophication of the lakes, which may jeopardize the quality of drinking water. In this study, superheated steam drying (SSD) technology is investigated as an alternative manure management method. Rapidly dried cow manure can be used as alternative fuel. Evaluations of energy payback time (EPBT) and life cycle assessment (LCA) of the SSD technology are presented in the SSD scenario and the results are compared with those of the direct field application (FA) of fresh manure and anaerobic digestion (AD). The heat required for the generation of superheated steam in the SSD scenario is provided from combustion of the dry manure to reduce energy costs. The results for the SSD process show 95% and 70% lower eutrophication and global warming potential in comparison to the FA scenario. Acidification potential for SSD turned out to be 35% higher than FA. The comparison of SSD with AD for their EPBT and normalized impacts indicated that the proposed SSD scenario has higher environmental sustainability than AD (70% lower impact), and is likely an economically better choice compared to conventional AD method (87% lower EPBT) for the future investment. Highlights: Life cycle assessment (LCA) is used for superheated-steam drying (SSD) process. Eutrophication potential for SSD is 95% lower than direct field application (FA). Global warming potential for SSD is 70% lower than FA. SSD has 70% lower environmental impact than anaerobic digestion (AD). Energy payback time for SSD is 87% lower than AD.